Evaluation of locomotion methods in virtual reality navigation environments: An involuntary position shift and task performance. Issue 155 (November 2021) - Kim, Yong Min; Lee, Yushin; Rhiu, Ilsun; Yun, Myung Hwan
Highlights: Effects of four locomotion methods on user safety and performance were examined Walking in place and running in place can cause involuntary movements of the user For each locomotion method, larger involuntary movements were found in the turning course than in the straight course Teleportation required the shortest task completion time, but the error time ratio was the largest The safety issue of the users' involuntary movement should be solved ABSTRACT: Navigation is a representative task in a virtual environment (VE). The locomotion methods affect the navigation performance and can cause involuntary movements by the users, which may cause critical safety problems. Thus, this study examined the effects of different locomotion methods on the users' involuntary position shift (IPS) and navigation performance in a VE. Twenty-one healthy participants performed the navigation task with four locomotion methods: walking in place (WIP), running in place (RIP), joystick, and teleportation. The results showed that a larger amount of IPS occurred with VE navigation under WIP and RIP conditions than joystick and teleportation conditions, which may cause critical safety problems, such as collisions with walls. Moreover, teleportation took the shortest task completion time, but its error time ratio was the largest. These results are expected to help develop basic guidelines for applying locomotion methods to specific situations and establishing safety precautions for virtual reality experiences.